Microscopic Investigation of Protein Function in C. elegans Using Fluorescent Imaging. Issue 1 (1st October 2015) - Luke, Cliff J.; O'Reilly, Linda P.
Abstract: Caenorhabditis elegans is a powerful model organism for studying human biology and disease due to its surprisingly high genetic homology to Homo sapiens . Its genetic amenability, small size, short generation time, and transparent body make it an ideal organism for multiple scientific disciplines. Fluorescent microscopy is essential for studying protein biological function. However, C. elegans, mainly due to its high motility, has been more difficult to adapt to fluorescence imaging, especially live‐imaging. We present here several protocols for the study of protein location, function and dynamics in context of a whole animal. These protocols, especially when combined with existing genetic procedures, can yield a great deal of insight in the physiological roles of proteins in C. elegans, which can be directly translated into mammalian systems. © 2015 by John Wiley & Sons, Inc.